Efektivitas Pelaksanaan Evaluasi Formatif dalam Pembelajaran Matematika di kelas XI MAN 2 Kota Padang - A’zima Ashari Fauzi; Nita Putri Utami (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to examine the effectiveness of formative assessment in mathematics learning for tenth-grade students at MAN 2 Kota Padang. A descriptive qualitative approach was used with data collected through observation, interviews, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings show that formative assessments were systematically implemented and aligned with learning objectives. Teachers employed various question types, especially essay questions, to assess students’ higher-order thinking skills. However, challenges such as limited time and lack of question variety were noted. It can be concluded that the formative assessment was fairly effective but requires further development in variation and technical support.